Epstein-Barr virus-driven lymphomagenesis in the context of human immunodeficiency virus type 1 infection - Petrara, Maria Raffaella; Freguja, Riccardo; Gianesin, Ketty; Zanchetta, Marisa; De Rossi, Anita (Frontiers in Microbiology, 2013)
Epstein–Barr Virus (EBV) is a ubiquitous human γ-herpes virus which establishes a life-long asymptomatic infection in immunocompetent hosts. In HIV-1 infected patients, the impaired immunosurveillance against EBV may favor the development of EBV-related diseases, ranging from lymphoproliferative disorders to B-cell Non-Hodgkin's lymphomas (NHL). Antiretroviral therapy (ART) has significantly modified the natural course of HIV-1 infection, resulting in decreased HIV-1 plasmaviremia, increased CD4 lymphocytes, and decreased opportunistic infections, indicating a restoration of immune functions. However, the impact of ART appears to be less favorable on EBV-related malignancies than on other AIDS-defining tumors (ADC), such as Kaposi’s Sarcoma, and NHL remains the most common cancer during the ART era. EBV-driven tumors are associated with selective expression of latent oncogenic proteins, but uncontrolled lytic cycle with virus replication and/or reactivation may favor cell transformation, at least in the early phases. Several host's factors may promote EBV reactivation and replication; besides immunodepression, inflammation/chronic immune stimulation may play an important role. Microbial pathogen-associated molecular patterns (PAMPs) and endogenous damage-associated molecular patterns (DAMPs), through Toll-like receptors (TLR), activate the immune system and may promote EBV reactivation and/or polyclonal expansion of EBV-infected cells. A body of evidence suggests that chronic immune stimulation is a hallmark of HIV-1 pathogenesis and may persist even in ART-treated patients. This review focuses on lymphomagenesis driven by EBV both in the context of the natural history of HIV-1 infection and in ART-treated patients. Understanding the mechanisms involved in the expansion of EBV-infected cells is a premise for the identification of prognostic markers of EBV-associated malignancies.